Multilobulated congenital epulis protruding from the maxillary anterior alveolar ridge in a four-day-old newborn: A case report - Khalid Almutairi; Rana Alshagroud; Fares Alrawashedah; Tariq Wahass (Oral and Maxillofacial Surgery Cases)
Congenital epulis is an exceedingly uncommon neoplasm that manifests in the oral cavity of neonates. The advancement in prenatal diagnostic techniques such as ultrasound and magnetic resonance imaging (MRI) allows for detection prior to birth. The most frequent site of manifestation is the anterior alveolar ridge of the maxilla, succeeded by the alveolar ridge of the mandible, and in rare cases, the tongue. There exist several theoretical proposals studying its histogenesis and potential causes, but they remain elusive. The case under discussion is a four-day-old female patient exhibiting a multilobulated, firm, pedunculated, mucosal-colored mass originating from the right anterior maxillary ridge and extending out from the mouth. The lesion posed an obstacle to normal feeding, although it fortunately did not impede the airway or respiration. The lesion was excised under general anesthesia and the specimen was forwarded to the histopathology laboratory where the diagnosis was confirmed. Seven weeks post-operation, the patient returned to our clinic exhibiting a fully healed wound. The prognosis for such a lesion is highly favorable, with no instances of recurrence documented in the literature. A multidisciplinary approach is required for the effective management of congenital epulis.